2015
DOI: 10.3758/s13415-015-0391-2
|View full text |Cite
|
Sign up to set email alerts
|

Distracted by danger: Temporal and spatial dynamics of visual selection in the presence of threat

Abstract: Threatening stimuli are known to influence attentional and visual processes in order to prioritize selection. For example, previous research showed faster detection of threatening relative to nonthreatening stimuli. This has led to the proposal that threatening stimuli are prioritized automatically via a rapid subcortical route. However, in most studies, the threatening stimulus is always to some extent task relevant. Therefore, it is still unclear if threatening stimuli are automatically prioritized by the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 82 publications
(125 reference statements)
3
37
1
Order By: Relevance
“…1b). With this paradigm, it was found that endogenously driven saccades to the target are slowed more by a threatening distractor than by a nonthreatening distractor (Hopkins, Helmstetter, & Hannula, 2016;Mulckhuyse & Dalmaijer, 2016). These results indicate that the threatening distractor captured covert attention automatically and thereby delayed the programming of a saccade to a different location.…”
Section: Saccade Latency In Visual Searchmentioning
confidence: 85%
See 3 more Smart Citations
“…1b). With this paradigm, it was found that endogenously driven saccades to the target are slowed more by a threatening distractor than by a nonthreatening distractor (Hopkins, Helmstetter, & Hannula, 2016;Mulckhuyse & Dalmaijer, 2016). These results indicate that the threatening distractor captured covert attention automatically and thereby delayed the programming of a saccade to a different location.…”
Section: Saccade Latency In Visual Searchmentioning
confidence: 85%
“…Most studies that investigated the effect of attentional capture by an emotional stimulus on oculomotor behavior found faster saccades to the emotional stimulus, reflecting enhanced attentional capture (Bannerman, Milders, de Gelder, et al, 2009;, 2010a, 2010bNummenmaa et al, 2009;Schmidt et al 2015Schmidt et al , 2017, slower saccades away from an emotional stimulus, reflecting delayed attentional disengagement (Bannerman et al, 2010a(Bannerman et al, , 2010bBelopolsky et al, 2011;Hopkins et al, 2016;Mulckhuyse & Dalmaijer, 2016;Schmidt et al, 2015Schmidt et al, , 2017, stronger deviations toward an emotional distractor (McSorley & van Reekum, 2013;Mulckhuyse et al, 2013), or away from an emotional distractor (Mulckhuyse et al, 2013;Nummenmaa et al, 2009;Schmidt et al, 2012). However, because of the set-up of most studies, emotional attention is never isolated from endogenous and exogenous attention, but rather most studies show an integration of emotion with endogenous or exogenous attentional processes (see also Brosch, Pourtois, Sander, & Vuilleumier, 2011).…”
Section: Summary and Discussion: Attentional Capture And Oculomotor Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Since saccade trajectories have been shown to indicate the amount of spatial attention that is allocated to a certain location (Van der Stigchel, Meeter, & Theeuwes, 2006), the results suggest a stronger attentional capture by fear-conditioned stimuli as compared to neutral ones. In a recent study, Mulckhuyse and Dalmaijer (2015) also demonstrated oculomotor capture by distractors that were previously associated with threat. Moreover, the presence of such distractors increased the latency of saccades to the target, suggesting that these distractors captured covert attention.…”
mentioning
confidence: 99%